The Influence of Return On Assets, Debt To Equity Ratio, and Sales Growth on Company Value with Dividend Payout Ratio as a Moderating Variable in the Property & Real Estate Sector on the Indonesian Stock Exchange - irna sulistiany; Edy Suryadi (Dinasti Publisher, 2025)
This study aims to examine the effect of return on assets, debt to equity ratio, and sales growth on company value with dividend payout ratio as a moderating variable. The study uses a quantitative method with an associative approach. The data type in this study is secondary data. The population of this study consists of all companies in the property and real estate sector. The sampling technique used in this study is purposive sampling. The sample consists of 30 companies. The results show that return on assets, debt to equity ratio, and sales growth significantly influence company value. Additionally, dividend payout ratio moderates the effect of return on assets, debt to equity ratio, and sales growth on company value.